2016
DOI: 10.1063/1.4967375
|View full text |Cite
|
Sign up to set email alerts
|

Plasma treatment effect on angiogenesis in wound healing process evaluated in vivo using angiographic optical coherence tomography

Abstract: Non-thermal atmospheric pressure plasma holds promise for promoting wound healing. However, plasma-induced angiogenesis, which is important to better understand the underlying physics of plasma treatment effect on wound healing, remains largely unknown. We therefore evaluated the effect of non-thermal plasma on angiogenesis during wound healing through longitudinal monitoring over 30 days using non-invasive angiographic optical coherence tomography imaging in vivo. We demonstrate that the plasma-treated vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Studies have shown that CAP can improve the viability, migration capacity, and reproduction capacity of keratinocytes and fibroblasts [30][31][32]. In addition, CAP has been shown to accelerate wound healing through recruitment of neutrophils, production of growth factors, and promotion of angiogenesis [33][34][35]. Therefore, CAP has a promising future in the application of skin wound healing [36].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CAP can improve the viability, migration capacity, and reproduction capacity of keratinocytes and fibroblasts [30][31][32]. In addition, CAP has been shown to accelerate wound healing through recruitment of neutrophils, production of growth factors, and promotion of angiogenesis [33][34][35]. Therefore, CAP has a promising future in the application of skin wound healing [36].…”
Section: Introductionmentioning
confidence: 99%
“…61 By monitoring structural changes such as wound dimension, epidermal migration, dermal-epidermal junction formation, vasodilation, vasoconstriction, and epithelization during wound healing process, OCT has been widely used as a noninvasive diagnostic tool in clinical applications. [62][63][64] It has also been utilized in the assessment of wound severity, depth, and microvascular structure in burn wounds through measurements of collagen bire-fringence reduction and fiber orientation. [65][66][67] Moreover, as chronic wound healing process is reliably associated with epithelialization, collagen deposition, and inflammation, OCT has a great potential for use in monitoring the progress in chronic wound healing by quantifying that information.…”
Section: New Optical Imaging Modalities For Chronic Wound Monitoringmentioning
confidence: 99%
“…Researchers from INP Figure 6. (a) Non-invasive angiographic OCT images and (b) stereoscopic images longitudinally acquired over 14 days after wound generation; relative depth in angiographic OCT images is color-coded as from yellow (superficial) to red (deep) [82].…”
Section: Plasma Interaction With Skin-related Cells/tissues In Vitromentioning
confidence: 99%
“…Figure 6 shows the en face vascular projections acquired from the angiographic OCT and matched stereoscopic images of the plasma and control wounds over 14 days. They found that the vascular wound area decease of plasma treated wound was more significant [82]. Up to date, very little is known about plasma-induced angiogenesis formation and a lot of work needs to be done in the future to understand the mechanism of plasma effect on angiogenesis.…”
Section: Plasma Interaction With Skin-related Cells/tissues In Vitromentioning
confidence: 99%